THE IMPACT OF EDUCATION PARAMETERS ON YOUTH UNEMPLOYMENT - Agranovich, M.L; Dreneva, A.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Youth unemployment is a pressing issue for most countries, including countries with strong economies. Relevant literature shows that unemployment is strongly correlated with educational parameters such as educational attainment, public expenditures on education, students' academic performance and cognitive abilities, and other economic and social factors. In our study, we carried out an analysis of economic and educational parameters to determine the most crucial predictors of the unemployment among the young population aged 25-34. The results of statistical analysis of data on participants and partners of the Organization for Economic Co-operation and Development showed significant differences among samples with different levels of education in the unemployment level, which was higher in the sample with lower educational level. The regression analysis revealed a significant influence of such predictors as the general unemployment of the population aged 25-72, the volume of public expenditures on education and the results in the international test of school achievements - PISA. Our findings indicate that educational parameters, along with the economic ones, have a pronounced impact on the labour market state, that allows us to suggest that measures for reducing unemployment can be extremely effective even at the stage of school education.